Maternal macronutrient intake during pregnancy is associated with neonatal abdominal adiposity: The growing up in singapore towards healthy outcomes (GUSTO) study. - Chen, Ling Wei (American Society for Nutrition, 2016)
10.3945/jn.116.230730